Green epithelium revealed by narrow-band imaging (NBI): a feature for practical assessment of extent of gastric cancer after H. pylori eradication - Yagi, Kazuyoshi (© Georg Thieme Verlag KG, 2018)

(untitled) (Endosc Int Open)
Background and study aims  Assessment of the extent of gastric cancer detected by endoscopy after successful eradication of H. pylori is often difficult even with narrow-band imaging (NBI)-magnifying endoscopy. Using the latter modality, it has often been noted that the cancerous area has a brownish color surrounded by green epithelium (GE). If the histological origin of this GE could be clarified, it could be of practical use for endoscopic assessment of the extent of cancer. Materials and methods  The endoscopic appearance of gastric cancer after eradication therapy was classified into four types: (A) cancer brownish, surrounding mucosa green; (B) cancer brownish, surrounding mucosa brownish; (C) cancer green, surrounding mucosa brownish; and (D) cancer green, surrounding mucosa green. A histological series of sections taken from tissues in each endoscopic view was stained with HE, and also for CDX2, MUC2, CD10 and MUC5AC. Staining intensity was evaluated by microscopy using a visual analog scale ranging from 0 to 3+: intensities of 0 and 1+ were rated as negative, and those of 2+ and 3+ as positive. Positive or negative immunostaining was examined for each type of endoscopic appearance A – D. Results  Among 42 lesions examined, 16 were type A, 18 type B, 6 type C and 2 type D. MUC2 was positive in the surrounding mucosa in 100 % of type A and D cases, but in only 28 % and 17 % of type B and C cases, respectively. Conclusions  GE observed by NBI-endoscopy corresponds to MUC2-positive mucosa and is thought to be a feature for practical assessment of the extent of cancer.